ANALISIS PERSEDIAAN BAHAN BAKU KEDELAI PADA AGROINDUSTRI PRODUK SUSU KEDELAI DAN TAHU CINA DI TAAS BANJER (STUDI KASUS UD. KEMBANG TAHU) - Anastasia Lamidja; Celsius Talumingan; Ribka M. Kumaat; Vicky R.B. Moniaga (Universitas Sam Ratulangi, 2014)
ABSTRACTThe objective of this study is to determine the raw materials inventory analysis of agro-industrial products soy milk and tofu chinese in Taas banjer (case study UD Kembang Tahu).Data collection was conducted for two months, from February to March, 2014. Data obtained ware primary and secondary data. The primary data obtained through the survey directly to the owner of the company UD. Kembang Tahu in Taas Banjer. Secondary data was obtained through company data, previous literature-literature and through the internet. Data analysis method used was the method of